Beginning JavaFX - PremKumar, Lawrence; Mohan, Praveen (Apress : Imprint: Apress, 2010)
The open source JavaFX platform offers a Java-based approach to rich Internet application (RIA) development-an alternative to Adobe Flash/Flex and Microsoft Silverlight. At over 100 million downloads, JavaFX is poised to be a significant player. Written by a JavaFX engineer and developer, this book is one of the first on the JavaFX platform to give you the following: The fundamentals of JavaFX scripting on desktop and mobile platforms Examples of RIAs using JavaFX Graphics Media and animation using JavaFX See how JavaFX gives you dynamic Java effects in your RIA development.